Antibacterial property of Hylocereus polyrhizus and Hylocereus undatus peel extracts - Mohd Maidin, Nurmahani; Osman, Azizah; Abdul Hamid, Azizah; Mohamad Ghazali, Farinazleen; Pak Dek, Mohd. Sabri (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Food-borne diseases have always been a major concern to the consumers, food safety authorities and food industries. Hylocereus spp or Pitaya peels are normally treated as wastes and will be discarded during processing. In this study, the antibacterial activity of ethanol, chloroform and hexane extracts from Hylocereus polyrhizus (red flesh pitaya) and Hylocereus undatus (white flesh pitaya) peels against nine pathogens was evaluated using disc diffusion method and broth micro-dilution method. Result from disc diffusion method showed that chloroform extracts from H. polyrhizus and H. undatus peel were found to exhibit good antibacterial activity where almost all the pathogens studied were successfully inhibited. Result of the minimum inhibitory concentration (MIC) showed that all extracts inhibit the growth of bacteria in the range of 1.25-10.00 mg/mL for all bacteria while their minimum bacteriacidal concentrations (MBC) indicated double of the MICs concentration except for B. cereus, L. monocytogenes and C. jejuni. Even though there is no clear trend indicating which bacteria were sensitive most to the extract, it can be concluded that chloroform extract of both H. polyrhizus and H. undatus peel showed the most potent antibacterial activity. Thus, these findings could be used further to understand the antibacterial property of the peel of pitaya fruits.